Upaya Meningkatkan Efektifitas Pembelajaran PKN melalui Media Digital pada Kelas XI IPS 1di SMA Negeri 3 Kerinci - Ramaina, Ramaina (Jurnal Ilmiah Dikdaya, 2022)
This research is a Classroom Action Research using digital learning media. Study this aim for know how enhancement effectiveness learning with utilisedigital learning media on eye PKN lessons. Focus indicator success is antus i 'm learning students, the effectiveness of the use of learning media, learning that can give results useful study _ and focused on participant educate and improveresults study learners.Study this use approach descriptive qualitative with design study action (action research)for explain about the effectiveness of learning with digital learning media and descriptive quantitative for describe results study students.Instrument study used are (1) sheet observation activity students, (2) sheets test.Technique data collection used namely (1) observation, (2) documentation, and (3) Post t test. The action was carried out in 2 cycles , each cycle of 2 meetings . Every meeting consists of 4 stages that is planning, implementation, observation and reflection. Research Subjects Class XI IPS 1 The place research at SMA N 3 Kerinci, Results study show that utilizationdigital learning media can Upgrade effectiveness learning and student learning outcomes, where the average student learning mastery increasessignificantly, thing the could proved on achievement results study student through test cycle Iand cycle II. Success results study student on cycle I reached an average of 70 or with a percentage70 % while level success achieved on cycle II experienced enhancement an average of 85 or85 %. So it can be concluded that the use ofdigital learning media can Upgrade effectiveness learning and learning outcomes of students in class XI IPS 1 at SMA 3 Kerinci .